2019
DOI: 10.1002/uog.20232
|View full text |Cite
|
Sign up to set email alerts
|

Systematic error and cognitive bias in obstetric ultrasound

Abstract: This issue of the Journal hosts an important systematic review assessing methodological aspects of studies constructing Doppler reference values for two clinically important vessels, the umbilical and fetal middle cerebral arteries. In this review, Oros et al. 1 developed a 24-item scale with which to assess the methodology of Doppler reference studies over three domains, namely, study design, statistics and reporting methods. Most of the included studies performed moderately for most of the items, which was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Blinding makes it difficult to bias results intentionally or unintentionally and so helps to ensure the credibility of measurements. Recently, a review of systematic error and cognitive bias in obstetric ultrasound suggested that expectation bias is pertinent to obstetric ultrasound studies.…”
Section: Introductionmentioning
confidence: 99%
“…Blinding makes it difficult to bias results intentionally or unintentionally and so helps to ensure the credibility of measurements. Recently, a review of systematic error and cognitive bias in obstetric ultrasound suggested that expectation bias is pertinent to obstetric ultrasound studies.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic observer error may occur if the observer has a preconceived idea of what a measurement ought to be, leading to adjustment of the reading by the observer 13 . Systematic errors affecting the efficacy of obstetric ultrasound have not been assessed extensively 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Systematic observer error may occur if the observer has a preconceived idea of what a measurement ought to be, leading to adjustment of the reading by the observer 13 . Systematic errors affecting the efficacy of obstetric ultrasound have not been assessed extensively 14 . Recently, expected‐value bias has been reported to affect biometry in clinical practice 13 and Doppler assessment for construction of reference ranges 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A high index of suspicion is required to diagnose HP in a general setting, where rates are lower. HPs may frequently be missed on imaging due to both anchoring bias (whereby the clinician clings to the initial diagnostic impression and fails to adjust their impression in light of subsequent information) and satisfaction of search bias (whereby the clinician stops searching for abnormalities once a diagnosis perceived as being likely has been reached) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%